Relative contribution of trends in myocardial infarction event rates and case fatality to declines in mortality: an international comparative study of 1·95 million events in 80·4 million people in four countries - Ximena Camacho, MMath; Lee Nedkoff, PhD; F Lucy Wright, DPhil; Nhung Nghiem, PhD; Emmalin Buajitti, MPH; Raphael Goldacre, MSc; Laura C Rosella, PhD; Olena Seminog, DPhil; Eng Joo Tan, PhD; Alison Hayes, PhD; Andrew Hayen, ProfPhD; Nick Wilson, ProfMBChB; et al. (Elsevier, 2022)
Summary: Background: Myocardial infarction mortality has declined since the 1970s, but contemporary drivers of this trend remain unexplained. The aim of this study was to compare the contribution of trends in event rates and case fatality to declines in myocardial infarction mortality in four high-income jurisdictions from 2002-15. Methods: Linked hospitalisation and mortality data were obtained from New South Wales (NSW), Australia; Ontario, Canada; New Zealand; and England, UK. People aged between 30 years and 105 years were included in the study. Age-adjusted trends in myocardial infarction event rates and case fatality were estimated from Poisson and binomial regression models, and their relative contribution to trends in myocardial infarction mortality calculated. Findings: 1 947 895 myocardial infarction events from a population of 80·4 million people were identified in people aged 30 years or older. There were significant declines in myocardial infarction mortality, event rates, and case fatality in all jurisdictions. Age-standardised myocardial infarction event rates were highest in New Zealand (men 893/100 000 person-years in 2002, 536/100 000 person-years in 2015; women 482/100 000 person-years in 2002, 271/100 000 person-years in 2015) and lowest in England (men 513/100 000 person-years in 2002, 382/100 000 person-years in 2015; women 238/100 000 person-years in 2002, 173/100 000 person-years in 2015). Annual age-adjusted reductions in event rates ranged from -2·6% (95% CI -3·0 to -2·3) in men in England to -4·3% (-4·4 to -4·1) in women in Ontario. Age-standardised case fatality was highest in England in 2002 (48%), but declined at a greater rate than in the other jurisdictions (men -4·1%/year, 95% CI -4·2 to -4·0%; women -4·4%/year, -4·5 to -4·3%). Declines in myocardial infarction mortality rates ranged from -6·1%/year to -7·6%/year. Event rate declines were the greater contributor to myocardial infarction mortality reductions in Ontario (69·4% for men and women), New Zealand (men 68·4%; women 67·5%), and NSW women (60·1%), whereas reductions in case fatality were the greater contributor in England (60% in men and women) and for NSW men (54%). There were greater contributions from case fatality than event rate reductions in people younger than 55 years in all jurisdictions, with contributions to mortality declines varying by country in those aged 55-74 years. Event rate declines had a greater impact than changes in case fatality in those aged 75 years and older. Interpretation: While the mortality burden of myocardial infarction has continued to fall across these four populations, the relative contribution of trends in myocardial infarction event rates and case fatality to declining mortality varied between jurisdictions, including by age and sex. Understanding the causes of this variation will enable optimisation of prevention and treatment efforts. Funding: National Health and Medical Research Council, Australia; Australian Research Council; Health Research Council of New Zealand; Canadian Institutes of Health Research, Canada; National Institute for Health Research, UK.